PANDANGAN KELUARGA PETANI TERHADAP PENDIDIKAN ANAK - Rofi, Sofyan (Universitas Muhammadiyah Jember, 2018)
Education is a conscious and planned effort to create both conducive atmosphere and process of learning so that learners can actively develop their potentials. These potentials include, for instance, developing their sense of spirituality, religiosity, self-control, noble character and skills all of which are profoundly needed by the learners themselves as well as by their society and country. The 9-year compulsory education is a program from the government to address the needs and challenges that await all individuals in the future. According to the national act no. 20/2003, the government seeks to improve the standard of the people’s life by requiring all Indonesian citizens of 7-12 as well as 12-15 years old to finish primary education with a 6 year program in elementary school and with 3 year program in junior high school. Nonetheless, without parental support it is hard to put such a program into practice. The support, however, may substantially influenced by the perceptions and beliefs of the parents regarding the importance of education. This is mostly the case in Jember regency whose community are mostly peasant. To unravel this issue, therefore, this study was conducted at SMP Muhammadiyah 6 Wuluhan whose students largely are from peasant community. More specifically, this study aimed to explore the perceptions and beliefs of students’ parents about the importance of education for their children. This study employed a case study methodology with the data obtained through interviews. The findings suggest that the students’ parents consider education is highly important for their children. Keyword : peasant, student parent, education